Prophylactic effects of dietary Isochrysis galbana on immersion-challenged red hybrid tilapia (Oreochromis spp.) with Streptococcus agalactiae by spleen-NMR-metabolomics - Ahamad Bustamam, Muhammad Safwan; Shaari, Khozirah; Chong, Chou Min; Monir, Md Shirajum; Pantami, Hamza Ahmed; Ismail, Intan Safinar (Springer Dordrecht, 2023)
This study explored the biomarkers and metabolic pathways from the tilapia spleen implicated by Streptococcus agalactiae infection and the immunoprophylactic efficacy of dietary Isochrysis galbana (IG) through nuclear magnetic resonance (NMR) metabolomics approach. Initially, the fish were divided into two groups (n = 34 per group) which were one fed with 2.5% IG-supplemented diet (IBC) and another with commercial diet as a control (CBC) for 14 days. The fish (n = 10) were then immersion-challenged with S. agalactiae for 7 days. The spleen was then harvested and subjected to 700-MHz 1H NMR for analysis. The results suggested that the survival rate of fish fed with IG-supplemented diets (IAC) was 55% higher than that of the commercial diet (CAC). The histological appearance of multiple organs also indicated the severity of S. agalactiae infection in CAC compared to IAC. Multivariate data analysis indicated that several metabolites such as isoleucine, valine, and leucine which are involved in valine, leucine, and isoleucine biosynthesis were significantly upregulated. Meanwhile, lactate and α-/β-glucose involved in pyruvate metabolism and glycolysis, respectively, were greatly downregulated, which could possibly be identified as bacterial infection biomarkers. These biomarkers exhibited minimal changes (21.4–38.2%) in IAC fish suggesting the prophylactic effects of the dietary IG against S. agalactiae observed in the fish spleen. Hence, the potential of IG as an immunomodulator in improving the tilapia health has been successfully determined through this study.